Management Deficiencies Hinder Growth in the Region - Wersonig, Klemens (Marketing & Menedzsment, 2019)
Lack of customer focus and inefficiently run businesses are among the biggest problems for doing business in Central and Eastern Europe. On the other hand, local managers are hard working and ambitious, the business environment is dynamic and women managers outperform male managers. These have been among the major findings of the research conducted in 6 European Union member countries by TARGET International Executive Search Group, together with Henley Business School. While there are some general characteristics of the region, there are also significant differences between the management cultures of Bulgaria, the Czech Republic, Hungary, Poland, Romania and Slovakia.